A Comprehensive Survey on Providing Efficient Driving Directions Using GPS and Driver`s Ability - Sivaiah, G; Rao, P Krishna (International Journal of Computer Sciences and Engineering, 2014)
Global positioning system (GPS) data can provide us valuable knowledge to understand the user. It also enables context-aware computing based on user’s present transportation mode and design of an innovative user interface for Web users. GPS-equipped taxis are employed as mobile sensors probing the traffic rhythm of a city and taxi drivers’ intelligence in choosing driving directions in the physical world. Here we mine smart driving directions from the historical GPS trajectories of a large number of taxis, and provide a user with the practically fastest route to a given destination at a given departure time. There are many problems we need to address with regard to driving directions such as finding nearest distance route between source and destination, traffic lights on route, direction turns on route, and checking weather conditions. Hence, a survey is conducted through which we can focus on the most important issue is finding efficient route driving directions.